We give a complete solution of the matrix equation AX+BX=0, where A, B ∈ C^mxn are two given matrices, X ∈ C^mxn is an unknown matrix, and denotes the transpose or the conjugate transpose. We provide a closed formula for the dimension of the solution space ofFernando De Terán...
a不许考我 Does not have to test me[translate] aThe solution of the first equation is U0(x) = Ax, but we set A = 0 because U0(x) = O(x2). We find also first等式的解答是U0 (x) =轴,但我们设置了A = 0,因为U0 (x) = O (x2)。 我们也find[translate]...
The solution of the differential equation\(y''-2y' y=0\) is A. \(y(x)=Ce^{x}\) B. \(y(x)=(C_1+xC_2)e^{x}\) C. \(y(x)=C_1e^x+C_2e^{-x}\) D. the solution does not exist. 相关知识点: 试题来源: 解析 B ...
The solution of the equationx2d2ydx2=logxwhenx=1,y=0anddydx=−1is View Solution The solution of the equation (x2−yx2)dy+(y2+x2y2)dx=0 View Solution solution of(x+y−1)dx+(2x+2y−3)dy=0is : View Solution The solution of the equationdydx+3y=cos2xis ...
百度试题 结果1 题目The solution of the matrix equation is X=A^(-1)B. 相关知识点: 试题来源: 解析反馈 收藏
A sharp simple criterion for a subclass of starlike functions Let A denote the class of functions that are analytic in the unit disc: If feA and where M0 is the strictly positive solution of the equation then or Z e U... P Mocanu,I Erb - 《Complex Variables & Elliptic Equations》 被...
The solution set of the equation ∣∣∣∣x372x276x∣∣∣∣=0 is A{2,−3,7} B{2,7,−9} C{−2,3,−7} Dnone of theseSubmit The solution set of the equation sin−1x=2tan−1x is A{1,2} B{−1,2} C{−1,1,0} D{1,12,0}Submit The solution set of the...
百度试题 结果1 题目 The solution of the equation 7x 7=8x can be expressed in the form x=logb77. What is b?( ) A. 715 B. 78 C. 87 D. 158 E. 157 相关知识点: 试题来源: 解析 C N/A. 反馈 收藏
The unique solution of the matrix equation AXB CXD = E is obtained in explicit form by means of the inversion of an n X n or m X m matrix from the coefficients of the Laurent expansions of ( λC A) 1 and ( λB D) 1 and the relative characteristic polynomial of λC A or λB...
is a positive integer, find the value of integer a. 相关知识点: 试题来源: 解析 a=2 or a=3 (2a+1)x=3ax−2, (−a+1)x=−2, Since it has solution, (−a+1)≠0, x=2a−1. Since the solution of equation (2a+1)x=3ax−2 is a positive integer and a is a integer...